FORMULASI SEDIAAN LOTION MENGGUNAKAN KOLAGEN TULANG IKAN PATIN (PANGASIUS SP) SEBAGAI PELEMBAB KULIT - Hepni Hepni (Indonesian Trust Health Journal, 2021)
Background: In general, people consume catfish meat as a source of protein and a high content of omega 3, while the bones are disposed of as waste. Collagen is a protein derivative that has the effect of maintaining skin elasticity. Objective: To find out whether the catfish bone collagen can be formulated into lotions which in certain consentration can moisturize and do not irritate the skin. Method: Extraction of collagen from catfish bones, characterization of collagen by infrared spectrophotometry, making collagen lotion of catfish bones with a concentration of 1%, 1.5%, 2.5%, 3.5% and evaluation of collagen lotion preparations and test the ability of the preparation to moisturize. skin using a Skin moisturizer detector (SG- ed statistically using the ANOVA test with SPSS 20 Free trial. Result: Catfish bones contained collagen in waves of 3250-3350 cm-1 and 1260-1630 cm-1 which indicated the presence of amine and amide groups. The statistical test results show the probability is smaller than 0.05. The highest humidity was in the FE formula which contained 3.5% collagen with a moisture percentage of 53.0% with a level of "Moist" but lower than the lotions on the market with a percentage of 54.3%. Conclusion: Catfish bone collagen can be formulated into oil-in-water (M/A) emulsion type lotion. Abstrak Pendahuluan: Secara umum masyarakat mengkonsumsi daging ikan patin sebagai sumber protein dan kandungan omega 3 yang tinggi, sedangkan tulangnya dibuang sebagai limbah. Kolagen merupakan salah satu turunan protein yang mempunyai efek untuk mempertahankan kekenyalan kulit. Tujuan: Untuk mengetahui apakah kolagen tulang ikan patin dapat diformulasikan kedalam sediaan lotion yang dalam konsentrasi tertentu dapat melembabkan dan tidak mengiritasi kulit. Metode: Ekstraksi kolagen dari tulang ikan patin, karakterisasi kolagen dengan spektrofotometri inframerah, pembuatan lotion kolagen tulang ikan patin dengan konsentrasi 1%, 1,5%, 2,5%, 3,5% dan evaluasi sediaan lotion kolagen serta uji kemampuan sediaan melembabkan kulit memakai alat Skin moisturizer detector (SG-7D ) serta hasilnya diuji secara statistik memakai uji ANOVA dengan SPSS 20 Free trial. Hasil: Tulang ikan patin mengandung kolagen pada gelombang 32503350 cm-1 dan 1260-1630 cm-1 yang menunjukkan adanya gugus amina dan amida. Hasil uji statistik menunjukkan probabilitas lebih kecil dari 0,05. Kelembaban tertinggi yaitu pada formula FE yang mengandung 3,5% kolagen dengan persentase kelembaban 53,0% dengan level ”Lembab” tetapi lebih rendah dari lotion yang beredar dipasaran dengan persentase sebesar 54,3%. Kesimpulan: Kolagen tulang ikan patin dapat diformulasi menjadi sediaan lotion tipe emulsi minyak dalam air (M/A).